2012
DOI: 10.1186/1471-2172-13-44
|View full text |Cite
|
Sign up to set email alerts
|

Fermented fish oil suppresses T helper 1/2 cell response in a mouse model of atopic dermatitis via generation of CD4+CD25+Foxp3+ T cells

Abstract: BackgroundAllergic skin inflammation such as atopic dermatitis (AD), which is characterized by pruritus and inflammation, is regulated partly through the activity of regulatory T cells (Tregs). Tregs play key roles in the immune response by preventing or suppressing the differentiation, proliferation and function of various immune cells, including CD4+ T cells. Recent studies report that fermentation has a tremendous capacity to transform chemical structures or create new substances, and the omega-3 polyunsatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 41 publications
1
43
0
1
Order By: Relevance
“…The spleen contains a range of immune cells and plays an important role in regulating the immune response. Because splenic enlargement or splenomegaly indicates abnormality of immune system function in AD (16, 17), we compared the change of morphological features of the spleen among the groups. The mice receiving excipient or GI7-L were found to have significantly enlarged spleens compared to those of the control group ( p <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The spleen contains a range of immune cells and plays an important role in regulating the immune response. Because splenic enlargement or splenomegaly indicates abnormality of immune system function in AD (16, 17), we compared the change of morphological features of the spleen among the groups. The mice receiving excipient or GI7-L were found to have significantly enlarged spleens compared to those of the control group ( p <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The differentiation, survival, and function of Treg cells are largely driven by IL‐2 and TGF‐β1 signals, which appear to directly regulate the expression of a master transcription factor FOXP3 . The activation of Tregs has been proved to be critical for downregulation of inflammatory process and the maintenance of peripheral tolerance in the skin allergic reaction . Tregs preferentially express the critical immunosuppressive cytokines TGFβ‐1, IL‐10, and IL‐35 .…”
Section: Treg Cells and Respective Cytokinesmentioning
confidence: 99%
“…The activation of Tregs has been proved to be critical for downregulation of inflammatory process and the maintenance of peripheral tolerance in the skin allergic reaction . Tregs preferentially express the critical immunosuppressive cytokines TGFβ‐1, IL‐10, and IL‐35 . Tregs can also directly inhibit differentiation, proliferation, and function of conventional T cells, including CD4 + and CD8 + T cells, through direct cell‐cell contact and down‐modulation of function of the APCs, especially DCs .…”
Section: Treg Cells and Respective Cytokinesmentioning
confidence: 99%
“…An interesting point is that even in the presence of CD28 signaling, rapamycin-treated T CD4 + cells can become anergic. In summary, it can be concluded that mTOR plays a central role in the fate of T CD4 (Table I) (10,15,19,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). As shown in Table I, several studies have been devised to find the mechanisms involved in determining T CD4 + cells differentiations, and factors like fatty acids and vitamins have been evaluated.…”
Section: Discussionmentioning
confidence: 99%